2010
DOI: 10.1680/stbu.2010.163.6.361
|View full text |Cite
|
Sign up to set email alerts
|

Current static design guidance for hollow-section joints

Abstract: The first edition of the International Institute of Welding (IIW) subcommission XV-E design recommendations on static strength of tubular joints was published in 1981. The second edition was published in 1989, which was the basis for the Cidect (International Committee for the Development and Study of Tubular Structures) design guides on the static strength of tubular joints in the early 1990s. Extensive research on tubular joints has been carried out all over the world in the last 20 years. There has hence be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(19 citation statements)
references
References 16 publications
0
16
0
3
Order By: Relevance
“…Both static design and fatigue design were covered. Zhao et al [337] summarized the third edition of IIW static design procedures for welded hollow-section joints. Research background on yield stresses, moment resistance of multi-planar joints, chord stress functions, overlap joints, and plate-to-tube joints were discussed.…”
Section: Tubular Jointsmentioning
confidence: 99%
“…Both static design and fatigue design were covered. Zhao et al [337] summarized the third edition of IIW static design procedures for welded hollow-section joints. Research background on yield stresses, moment resistance of multi-planar joints, chord stress functions, overlap joints, and plate-to-tube joints were discussed.…”
Section: Tubular Jointsmentioning
confidence: 99%
“…8. For the unreinforced joint, the resistance according to the deformation limit criteria of 3 % b 0 proposed by Lu et al [16] and confirmed by Zhao et al [7] was 216.76 kN and 125.53 kN according to Eurocode 3, part 1-8. The same value is obtained for the reinforced joints considering that t 0 and t p are equals.…”
Section: Discussionmentioning
confidence: 79%
“…Numerous international design codes explicitly cover the design of tubular joints ( [3], [5]). Wardenier et al [6] and Zhao et al [7] presented the tubular joint design latest standards incorporating the IIW (2009) improvements [5]. More recently, two codes focusing on tubular joints design were also updated with the recent advances in this field ( [8], [9]).…”
Section: Introductionmentioning
confidence: 99%
“…Based on the numerical database collated by Lu et al [39], the service load -assumed to be 1/1.5 of the ultimate joint resistance determined according to the 3 %d 0 rule -produced an indentation of less than 1 %d 0 . Zhao et al [40] later assessed the 1 %d 0 limit-based serviceability criterion and concluded that a better correlation with the experimental results was obtained when using only the 3 % deformation limit criterion. Since then, the 1 %d 0 rule has rarely been used to evaluate experimental results.…”
Section: Articlementioning
confidence: 99%